Proceedings of the 1st European workshop on HCI design and evaluation : the influence of domain on human computer interaction design anf evaluation - Zaphiris, Panayiotis; Christou, Georgios; Law, Effie Lai-Chong (My University, 2011)
E-learning is becoming very important in fields where access to learning materials needs to be brought about effectively and efficiently. Our experience in dealing with e-learning systems of different types has shown that several aspects influence the design and the evaluation of such systems, primarily the educational aspect, since the main purpose of such systems is to achieve educational goals. We are well aware that specific conceptual models and practical protocols are needed, capable of considering all the aspects that influence design and evaluations of e-learning systems.As a consequence, in the last few years we have developed the TICS (Technology, Interaction, Content, Services) framework and the eLSE (e-Learning Systematic Evaluation) methodology that, taking into account the most important aspects of e-learning system quality, aim at guiding designers and evaluators.
Keywords: Humanities; Educational technology; Education--Computer network resources